Effects of drip irrigation on spring soybean (Glycine max (L.) Merr.) growth and soil physical indexes of Heilongjiang province of China - Zhu, Baoguo; Zheng, Chunfeng; Jia, Huibin; Meng, Qingying; Wang, Nannan; Kuang, Enjun; Zhang, Libo; Shen, Xiaohui; Gao, Xuedong (Bangladesh Journal of Botany, 2019)
Effects of different drip irrigation on the growth, development and yield of spring soybean was carried out by measuring the growth index and soil physical characteristics index of spring soybean (Glycine max (L.) Merr.). On the basis of natural precipitation in the same year, 4 drip irrigation levels, namely W1 (0 mm), W2 (200 mm), W3 (400 mm) and W4 (600 mm) were established. From flowering to the pod stage of soybean, a significant increase in the soil moisture and a reduction in the soil hardness and bulk density were observed. Though the difference between W3 and W4 was not significant, drip irrigation affected soil physical properties followed W4 > W3 > W2 > W1. Improved growth index including plant height, above-ground biomass and leaf area of soybean was also observed, but excessive drip irrigation triggered the decline of leaf area index and above-ground biomass. Changes caused in the soil physical properties due to drip irrigation affected soybean growth, which resulted a positive action on yield. Compared with W1 treatments, soybean yield in the different irrigation in the W3, W4 and W2 in the year 2015 and 2016 were increased by 83.68 and 46.99%, 61.58 and 39.47%, 23.51 and 20.21%, respectively. Based on the results of the present experiment it was observed that W3 treatment (irrigation rate 400 mm) was the best one for the improved crop yield of soybean.